2017
DOI: 10.1002/hyp.11399
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration into frozen soil: From core‐scale dynamics to hillslope‐scale connectivity

Abstract: Infiltration into frozen soil is a key hydrological process in cold regions. Although the mechanisms behind point‐scale infiltration into frozen soil are relatively well understood, questions remain about upscaling point‐scale results to estimate hillslope‐scale run‐off generation. Here, we tackle this question by combining laboratory, field, and modelling experiments. Six large (0.30‐m diameter by 0.35‐m deep) soil cores were extracted from an experimental hillslope on the Canadian Prairies. In the laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
4
20
0
Order By: Relevance
“…Such an effect likely contributed to the sequential increase in runoff ratios during melt events at the Stauffer and Triple G sites (Table 3). These observations of the refreezing of infiltrated meltwater are generally consistent with the "pre-fill" phase of the conceptual model of runoff generation in frozen soil proposed by Appels et al (2018), in which the refreezing of initially infiltrated water is necessary to reduce infiltrability before runoff can occur. To the best of our knowledge, no other study has demonstrated the time sequencing of this infiltration-refreezing effect on enhancing subsequent runoff partitioning over multiple snowmelt events.…”
Section: Snowmelt Partitioning and Runoff Generationsupporting
confidence: 86%
“…Such an effect likely contributed to the sequential increase in runoff ratios during melt events at the Stauffer and Triple G sites (Table 3). These observations of the refreezing of infiltrated meltwater are generally consistent with the "pre-fill" phase of the conceptual model of runoff generation in frozen soil proposed by Appels et al (2018), in which the refreezing of initially infiltrated water is necessary to reduce infiltrability before runoff can occur. To the best of our knowledge, no other study has demonstrated the time sequencing of this infiltration-refreezing effect on enhancing subsequent runoff partitioning over multiple snowmelt events.…”
Section: Snowmelt Partitioning and Runoff Generationsupporting
confidence: 86%
“…Dunkerley et al have demonstrated that the more compact the soil, the smaller its porosity and the lower the steady infiltration rate [40]. With a higher aggregate content, the number of soil pores increases, resulting in improved soil ventilation and permeability and in enhanced soil stability, preventing the formation of soil surface crusts [41]. The aggregate content was highest in the soil from the L. gmelinii site, which therefore had the highest seepage stabilization rate.…”
Section: Soil Infiltration Rates Under Different Forest Typesmentioning
confidence: 99%
“…The aggregate content was highest in the soil from the L. gmelinii site, which therefore had the highest seepage stabilization rate. demonstrated that the more compact the soil, the smaller its porosity and the lower the steady infiltration rate [41]. With a higher aggregate content, the number of soil pores increases, resulting in improved soil ventilation and permeability and in enhanced soil stability, preventing the formation of soil surface crusts [42].…”
Section: Soil Infiltration Rates Under Different Forest Typesmentioning
confidence: 99%
“…Additional information on the generation of the 2 m and 0.25 m DEMs can be found in . The soils are Orthic Brown Chernozems (Ayres et al, 1985), specifically Swinton silt loam in the upper four-fifths of the hillslopes, where the solum is developed within loess, and Haverhill loam in the lower fifth of the hillslope, where past erosion has resulted in the solum extending into the underlying loamy till (McConkey et al, 1997). The surficial 0-15 cm soil layer consists of 50.4 % silt, 31.4 % sand, and 18.2 % clay, has a bulk density of 1.22 g cm −3 , and has a saturated hydraulic conductivity of 14.2 mm h −1 .…”
Section: The Swift Current Hillslopesmentioning
confidence: 99%
“…The year 2011 marked the final year of regular monitoring of the hillslopes by the Swift Current Research and Development Centre of Agriculture and Agri-food Canada. In 2013 and 2014, monitoring of runoff, snowpack characteristics, and soil moisture was undertaken in collaboration with the University of Saskatchewan; these data are presented separately (Appels et al, 2017;. If regular monitoring of the hillslopes resumes, the data repository will be updated accordingly.…”
Section: The Swift Current Hillslopesmentioning
confidence: 99%